Professor Nikola Saranov – the Teacher and the Long-lasted Oblivion - Vuchkov, Veselin (Yearbook of the Law Department, 2020)
The present study presents the professional career of one of the most famous lecturers in the Law Faculty of the Sofia University “St. Kliment Ohridsky” till 1944 – namely Professor Nikola Saranov (1895–1974). Under detailed consideration is his professional career and the gradual way in which he has been established as a leading lecturer of the discipline Criminal court procedure. Professor Saranov has also introduced a lecture course in Criminal studies in Bulgaria. Following the coup d’etat of 9 September 1944 he has been gradually forced to quit his lecturing at the Law Faculty. In the study under consideration are documents in support of the consequences from this act, in particular monitoring and repressions on behalf of the State Security Service almost until the death of the professor in 1974. These activities of the repressive state machine are applied also to relatives and family members of the professor. Under consideration are also the various interests of Professor Saranov in different areas, including towards the short career of a judge of the national poet Ivan Vasov in the town of Bercovitsa in the period 1879–1880, with regard to which the professor issues a study in the Yearbook of the Law Faculty of the Sofia University in 1943.